ANALYSIS OF CONSUMER PREFERENCE AND CONSUMER ACCEPTANCE OF HALAL NATURAL BATH SOAP - Uzwatania, Fina; Ginantaka, Aditia; Awaludin, Awaludin (Jurnal Pertanian, 2018)
The increase of number of Bath Soap Producer in Indonesia, giving many option for consumer to choose the Bath Soap product. Preference Analysis is needed to be conducted for new Bath Soap Product to survive in the competition. This research aims to identify the consumer acceptance based on sensory attributes of  Natural Bath Soap that can affect the consumer, to analyze the attributes that into consumer consideration to choose Bath Soap Product, and to design a Halal and Natural Bath Soap. The first stage of this research is Consumer Preference Analysis of Natural Bath Soap. The second stage of this research is designing a Halal and Natural Bath Soap which it is attributes matched with the Consumer Preference Analysis Result. The analysis is consist of Organoleptic Test (Hedonic Test) and Quality Test for water content, FFA, alkaline free, and pH. The consumer preference analysis result shows that 25 from 30 consumer (83.3%) choose Oval shape Bath Soap, Honey was choose as active ingredient by 86.7% of consumer, and 60% of the consumer is prefer Lemon Grass for the Bath Soap aroma. Hedonic test result shows that every attributes does not have any significant effect to the consumer except the bath soap shape.